Parliamentarizing the Estate Diet: The debate on plenum plenorum in late 19th-century Finland. Issue 3 (27th May 2017) - Pekonen, Onni
Abstract : This article examines the transformation of estate assemblies into parliaments by analysing the case of the late 19th-century Diet of Finland. Furthermore, it positions the procedural discussions of the peripheral Finnish Diet within a wider European debate on parliaments and parliamentarism. While parliamentary government and the dissolution of Europe's last four-estate representation were largely out of the question in the Finnish Grand Duchy of the Russian Empire, revisions and innovations on Diet rules and practices formed an essential means to introduce elements of modern parliaments within the obsolete estate system. By analysing Finnish Diet and press discussions, the article re-examines the significance and reception of the Swedish Riksdag institution of plenum plenorum, the joint discussion of all four estates, in Finland. The article highlights a struggle between two concepts of deliberation. A liberal group organized around the newspaper Helsingfors Dagblad used plenum plenorum to challenge their Fennoman opponents' consensual idea of deliberation and the Diet's deliberative model, which was based on committee negotiation. The Dagbladists advocated plenum plenorum in order to transform the estates into a single debating parliamentary assembly.